A meta‐analysis of the criterion‐related validity of prehire work experience. Issue 4 (3rd May 2019) - Van Iddekinge, Chad H.; Arnold, John D.; Frieder, Rachel E.; Roth, Philip L.
Abstract: Organizations frequently screen or select job applicants based on their work experience. Despite this, surprisingly little is known about the criterion‐related validity of prehire experience, which reflects the amount, duration, or type of experience workers have acquired before they enter a new organization. To address this critical gap in the literature, we used meta‐analysis to synthesize data from 81 independent samples that reported relations between prehire experience and performance or turnover. Results revealed overall corrected correlations of .06 for job performance ( k = 44, n = 11, 785), .11 for training performance ( k = 21, n = 8, 176), and .00 for turnover ( k = 32, n = 11, 676). Measures that capture prehire experience with tasks, jobs, or occupations relevant to workers' current position also are only weakly related to the outcomes (e.g., ρ ¯ ̂ = .07 for job performance). Two exceptions to our main findings are that (a) prehire experience is somewhat more predictive of job performance when workers first start a new job and (b) measures of task‐level experience predict training performance, although these results are based on small subsets of primary studies. Overall, the present findings suggest that the types of prehire experience measures organizations currently use to screen job applicants generally are poor predictors of future performance and turnover. We therefore caution organizations from selecting employees based on such measures unless more positive evidence emerges.